The Expression Pattern of Surface Markers in Canine Adipose-Derived Mesenchymal Stem Cells - Krešić, Nina (Int J Mol Sci, 2021)
The influence of cultivation on the expression pattern of canine adipose-derived mesenchymal stem cells (cAD-MSCs) surface markers, contributing to, among others, the promotion of growth, proliferation, differentiation and immunomodulatory mechanisms of an excellent therapeutic, is still unknown. To fill the gap, we investigated CD90, CD44, CD73, CD29, CD271, CD105, CD45 and CD14 patterns of expression at the protein level with flow cytometry and mRNA level using a real-time polymerase chain reaction array. Gentle variations of expression occurred during cultivation, along with increased CD90, CD44 and CD29 expression, low and decreasing CD271 and CD73 expression and a decrease of initially high CD105. As expected, CD45 and CD14 were not expressed by cAD-MSCs. Interestingly, we discovered a significant decrease of CD73 expression, compared to early (P1–P3) to late (P4–P6) passages, although the CD73 gene expression was found to be stable. The percentage of positive cells was found to be higher for all positive markers up to P4. As CD73′s one important feature is a modulation from a pro-inflammatory environment to an anti-inflammatory milieu, the expression of CD73 in our conditions indicate the need to consider the time cells spend in vitro before being transplanted into patients, since it could impact their favourable therapeutical properties.